1986
DOI: 10.1351/pac198658091267
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic and metal organic photochemistry in industry

Abstract: Photochemical production processes are still extremely rare.With three examples from our own research laboratories illustration is made, how the acceptance of photochemical methodology can be increased. A diastereoselective photocyclisation and two newly designed organometallic photoinitiators succeeded because they overcome drawbacks of conventional operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 20 publications
1
42
0
Order By: Relevance
“…Product studies and trapping experiments with 2,2,6,6-tetramethylpiperidine N-oxide (TMPO) have, however, indicated that titanocenes with perfluorinated Ph groups behave quite differently [4]. Since no organic radicals could be trapped, the question arose by which mechanism the fluorinated diphenyltitanocenes initiated polymerization.…”
Section: Photochemical Ring Slippage Of Bis(pentafluoropheny1)titanocmentioning
confidence: 99%
“…Product studies and trapping experiments with 2,2,6,6-tetramethylpiperidine N-oxide (TMPO) have, however, indicated that titanocenes with perfluorinated Ph groups behave quite differently [4]. Since no organic radicals could be trapped, the question arose by which mechanism the fluorinated diphenyltitanocenes initiated polymerization.…”
Section: Photochemical Ring Slippage Of Bis(pentafluoropheny1)titanocmentioning
confidence: 99%
“…[37][38][39][40] A radically different class of cationic photoinitiators was developed by workers at the Ciba-Geigy Corporation. [41][42][43] Ferrocenium salts (XI) undergo photolysis to generate an iron-based Lewis acid with the loss of the arene ligand (eq 16). Coordination of this latter species with an epoxide monomer is followed by ring-opening polymerization.…”
mentioning
confidence: 99%
“…The absorption spectrum of complex (I) is similar to those all five ironarene complexes studied. 15 proposed a mechanism for the initiation in epoxide photopolymerization with the iron-arene complex as a photoinitiator, as shown in Scheme 1. epoxides during the photolytic step, is formed. Ring opening and polymerization reaction could thus start in the ligand sphere of the iron cation leading to cyclopolyethers.…”
Section: Resultsmentioning
confidence: 99%